Management of Learning Outcomes through SIJAGU PAI Design and Implementation of a Digital Reporting System for Islamic Religious Education - Barokah, Miftahul; Manshur, Umar (Journal of Educational Management Research, 2025)
The rapid advancement of digital technology has transformed educational reporting systems, resulting in increased transparency and efficiency. This study aims to design and implement SIJAGU PAI, a digital reporting system that enhances objectivity, accuracy, and collaboration in Islamic Religious Education. Using a qualitative case study approach, data were collected through interviews, observations, and documentation involving teachers, students, and parents. Findings reveal that SIJAGU PAI simplifies grade input, facilitates real-time communication, and visually represents student progress, fostering collaboration and trust among stakeholders. The application integrates faith-based design principles with data-driven transparency, bridging spiritual values and digital functionality. The study contributes to the development of an Islamic-oriented digital education model that prioritizes accountability and inclusivity. It is recommended that future implementations expand the system’s features for broader institutional integration and adopt adaptive analytics to support continuous quality improvement in religious education management.